Patients with bulimia nervosa do not show typical neurodevelopment of cognitive control under emotional influences. (30th August 2017) - Dreyfuss, Michael F.W.; Riegel, Melissa L.; Pedersen, Gloria A.; Cohen, Alexandra O.; Silverman, Melanie R.; Dyke, Jonathan P.; Mayer, Laurel E.S.; Walsh, B. Timothy; Casey, B.J.; Broft, Allegra I.
Abstract: Bulimia nervosa (BN) emerges in the late teen years and is characterized by binge eating and related compensatory behaviors. These behaviors often co-occur with periods of negative affect suggesting an association between emotions and control over eating behavior. In the current study, we examined how cognitive control and neural processes change under emotional states of arousal in 46 participants with (n=19) and without (n=27) BN from the ages of 18–33 years. Participants performed a go/nogo task consisting of brief negative, positive and neutral emotional cues and sustained negative, positive and neutral emotional states of arousal during functional magnetic resonance imaging (fMRI). Overall task performance improved with age for healthy participants, but not for patients with BN. These age-dependent behavioral effects were paralleled by diminished recruitment of prefrontal control circuitry in patients with BN with age. Although patients with BN showed no difference in performance on the experimental manipulations of negative emotions, sustained positive emotions related to improved performance among patients with BN. Together the findings highlight a neurodevelopmental approach towards understanding markers of psychopathology and suggest that sustained positive affect may have potential therapeutic effects on maintaining behavioral control in BN. Highlights: Patients with BN fail to show a typical improvement in cognitive control with age. Reduced recruitment of prefrontal circuitry underlies this behavioral trajectory. Cognitive control of patients with BN improves under positive emotions.